Gender and age normalization and ventilation efficiency during exercise in heart failure with reduced ejection fraction. (1st January 2020) - Salvioni, Elisabetta; Corrà, Ugo; Piepoli, Massimo; Rovai, Sara; Correale, Michele; Paolillo, Stefania; Pasquali, Mario; Magrì, Damiano; Vitale, Giuseppe; Fusini, Laura; Mapelli, Massimo; Vignati, Carlo; et al.
Abstract: Aims: Ventilation vs. carbon dioxide production (VE/VCO2 ) is among the strongest cardiopulmonary exercise testing prognostic parameters in heart failure (HF). It is usually reported as an absolute value. The current definition of normal VE/VCO2 slope values is inadequate, since it was built from small groups of subjects with a particularly limited number of women and elderly. We aimed to define VE/VCO2 slope prediction formulas in a sizable population and to test whether the prognostic power of VE/VCO2 slope in HF was different if expressed as a percentage of the predicted value or as an absolute value. Methods and results: We calculated the linear regressions between age and VE/VCO2 slope in 1136 healthy subjects (68% male, age 44.9 ± 14.5, range 13–83 years). We then applied age‐adjusted and sex‐adjusted formulas to predict VE/VCO2 slope to HF patients included in the metabolic exercise test data combined with cardiac and kidney indexes score database, which counts 6112 patients (82% male, age 61.4 ± 12.8, left ventricular ejection fraction 33.2 ± 10.5%, peakVO2 14.8 ± 4.9, mL/min/kg, VE/VCO2 slope 32.7 ± 7.7) from 24 HF centres. Finally, we evaluated whether the use of absolute values vs. percentages of predicted VE/VCO2 affected HF prognosis prediction (composite of cardiovascular mortality + urgent transplant or left ventricular assist device). We did so in the entire cardiac and kidney indexes score population and separately in HF patients with severe (peakVO2 < 14 mL/min/kg, n = 2919, 61.1 events/1000 pts/year) or moderate (peakVO2 ≥ 14 mL/min/kg, n = 3183, 19.9 events/1000 pts/year) HF. In the healthy population, we obtained the following equations: female, VE/VCO2 = 0.052 × Age + 23.808 ( r = 0.192); male, VE/VCO2 = 0.095 × Age + 20.227 ( r = 0.371) ( P = 0.007). We applied these formulas to calculate the percentages of predicted VE/VCO2 values. The 2‐year survival prognostic power of VE/VCO2 slope was strong, and it was similar if expressed as absolute value or as a percentage of predicted value (AUCs 0.686 and 0.690, respectively). In contrast, in severe HF patients, AUCs significantly differed between absolute values (0.637) and percentages of predicted values (0.650, P = 0.0026). Moreover, VE/VCO2 slope expressed as a percentage of predicted value allowed to reclassify 6.6% of peakVO2 < 14 mL/min/kg patients (net reclassification improvement = 0.066, P = 0.0015). Conclusions: The percentage of predicted VE/VCO2 slope value strengthens the prognostic power of VE/VCO2 in severe HF patients, and it should be preferred over the absolute value for HF prognostication. Furthermore, the widespread use of VE/VCO2 slope expressed as percentage of predicted value can improve our ability to identify HF patients at high risk, which is a goal of utmost clinical relevance.